2017
DOI: 10.1002/jctb.5170
|View full text |Cite
|
Sign up to set email alerts
|

Glucose oxidase effect on treatment of textile effluent containing reactive azo dyes byPhanerochaete chrysosporium

Abstract: BACKGROUND Chemically different types of dyes have been proven to be degraded by peroxidases of Phanerochaete chrysosporium. Hydrogen peroxide is required as a co‐substrate for peroxidases during the oxidation process. RESULTS Investigating the effect of glucose oxidase (GOx) (EC 1.1.3.4) on treatment of textile effluent containing recalcitrant diazo and azo dyes by P. chrysosporium was the main aim of this research. The effects of glucose, GOx and Mn2+ on chemical oxygen demand (COD), decolorization and manga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Degradation of mycotoxins in oxalate and citrate is of physiological relevance since, in nature, the fungi expressing MnPs can also produce these two compounds in their cellular metabolism [ 22 ]. Additionally, it has been reported that gluconic acid, cellobionic acid, and other organic acids as well, can aid manganese peroxidases to exert their degradation on lignin molecules [ 31 ]. This allows the fungi to use manganese peroxidases, in assistance with these naturally occurring molecules, to break the lignin barrier apart and capture energy from the plant cell wall polysaccharides [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Degradation of mycotoxins in oxalate and citrate is of physiological relevance since, in nature, the fungi expressing MnPs can also produce these two compounds in their cellular metabolism [ 22 ]. Additionally, it has been reported that gluconic acid, cellobionic acid, and other organic acids as well, can aid manganese peroxidases to exert their degradation on lignin molecules [ 31 ]. This allows the fungi to use manganese peroxidases, in assistance with these naturally occurring molecules, to break the lignin barrier apart and capture energy from the plant cell wall polysaccharides [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…5B) because the activity of MnP in the P system after 3 h treatment was higher than the initial amount. The effect of active pyranose 2-oxidase on MnP is same as MnP with glucose oxidase (Ansari et al 2016(Ansari et al , 2017. In the C system, LiP and MnP of 3 h treatment was 0.021 IU/mL and 0.75 IU/mL.…”
Section: Residual Enzyme Activities After Pyranose 2-oxidase Lignin-dmentioning
confidence: 86%
“…[90][91][92][93][94][95][96] One study found that MnP of P. Chrysosporium was the main enzyme involved in the discoloration of textile dyes. 97 This crude or purified enzyme's potential has also been reported, mainly to discolor various types of synthetic dyes. 93 In the study directed by Zhang et al, 85 MnP crude and purified from the fungus Cerrena unicolor BBP6 was used in the discoloration of solutions of Congo red dyes, MO, Remazol bright blue R, bromophenol blue, and crystal violet.…”
Section: Manganese Peroxidasementioning
confidence: 97%